Kombinovana detekcija HLA-B27, ESR i CRP kao biohemijskih i imunogenetskih markera u pomoćnoj dijagnozi ankilozantnog spondilitisa: HLA-B27, ESR, and CRP in Ankylosing Spondylitis - Wang, Muchuan; Yao, Siyuan; Gao, Chengao; Wang, Yipeng (Journal of Medical Biochemistry, 2025)
Background: Ankylosing spondylitis (AS) is a chronic inflammatory disease in which early diagnosis is often challenging due to atypical clinical manifestations. Laboratory biomarkers such as human leukocyte antigen-B27 (HLA-B27), erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) play an essential role in diagnostic evaluation.Methods: A total of 120 AS patients and 100 healthy controls were enrolled. Venous blood samples were analyzed for HLA-B27 (flow cytometry), ESR (Westergren method), and CRP (immunoturbidimetry). The Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) was assessed, and diagnostic performance was evaluated using receiver operating characteristic (ROC) curve analysis.Results: HLA-B27 positivity was significantly higher in the AS group than in controls (92.5% vs. 5.0%, P